Yahoo奇摩 網頁搜尋

  1. ...: -8 = 1 - 9 = 1² - 3² (ii) Factorize the expression : m² - 2m - 8 = m² - 2m + 1² - 3² = m² - 2m(1...

    分類:科學及數學 > 數學 2020年07月31日

  2. ...quot;沒甚麼",因為It is worth it這類片語式的表達只是一種 expression 附帶表達講者對主題句子/內容的情緒/意義表達。中文是"我感到真是好值得...

    分類:社會及文化 > 語言 2019年11月22日

  3. ...; 1 --------------- (2) I suppose you have already found the expression for Vb/Va in part (d). Let this be f, say. i.e. Vb...

    分類:科學及數學 > 物理學 2018年04月13日

  4. Sol A=√(x-1),B=√x,C=√(x+1) AB=√(x^2-x) BC=√(x^2+x) C^2-B^2=1 A^2-B^2=-1 √(x-1)/(√(x+1)-√x))+(√(x+1)/(√(x-1)+√x)) =A/(C-B)+C/(A+B) =(AC+AB)/(C^2...

    分類:科學及數學 > 數學 2017年09月13日

  5. Find out from the given arithmetic expression by the rule of division/multiplication first on ie:-(42 divided by 6); and...

    分類:社會及文化 > 語言 2017年10月04日

  6. ... as a conjunction (http://dictionary.cambridge.org/grammar/british-grammar/as-and-as- expressions /as) As I was just saying, I think the proposal...

    分類:社會及文化 > 語言 2017年08月19日

  7. ... equations (1) and (2), it shows that the given expression for V satisfies the equation dV/dt = (q/m)(V x B...

    分類:科學及數學 > 物理學 2017年04月11日

  8. (a) (i) (x - 4)(x - 6) = x² - 6x - 4x + 24 = x² - 10x + 24 ∴ (x - 4)(x - 6) = x² - 10x + 24........(1) (ii) (x - 2)(x - 8) = x² - 8x - 2x + 16 = x² - 10x + 16 ∴ (x - 2)(x - 8) = x² - 10x + 16.........(2) (b) (x - 2)(x - 4)(x - 6)(x - 8) + 16 = [(x - 4)(x - 6)][(x - 2)(x - 8)] + 16...

    分類:科學及數學 > 數學 2017年01月05日

  9. ...suitable for me in this course.I'll have a greater variety of expressions to use and my writing will be clearer and more organized...

    分類:社會及文化 > 語言 2016年12月29日

  10. ... the things that they say. "Utterance" is the expression in words of ideas, thoughts, and feelings. ...

    分類:社會及文化 > 語言 2017年02月03日